2013
DOI: 10.1002/term.1688
|View full text |Cite
|
Sign up to set email alerts
|

PEG hydrogel degradation and the role of the surrounding tissue environment

Abstract: Poly(ethylene glycol) (PEG)-based hydrogels are extensively used in a variety of biomedical applications due to ease of synthesis and tissue-like properties. Recently, there have been varied reports regarding PEG hydrogel’s degradation kinetics and in vivo host response. In particular, these studies suggest that the surrounding tissue environment could play a critical role in defining the inflammatory response and degradation kinetics of PEG implants. In the present study we demonstrated a potential mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 16 publications
0
92
0
1
Order By: Relevance
“…The histological data we collected as part of this study showed that the increase in MTR values and macromolecular ratios are associated with the extent of infiltrating cells in the capsule region. These immune cells consist of macrophages, neutrophils or dendritic cells [52]. Although MRI currently is not able to identify these cells, a distinctive difference was observed in both MTR and macromolecular ratio between the immunosuppressed group and the non-immunosuppressed groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The histological data we collected as part of this study showed that the increase in MTR values and macromolecular ratios are associated with the extent of infiltrating cells in the capsule region. These immune cells consist of macrophages, neutrophils or dendritic cells [52]. Although MRI currently is not able to identify these cells, a distinctive difference was observed in both MTR and macromolecular ratio between the immunosuppressed group and the non-immunosuppressed groups (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo degradation rates of polymers could be faster than in vitro; the higher in vivo degradation rate has been explained by the effects caused by cellular and enzymatic activities found in the body 16 . Traditionally, it is believed that PEG-based hydrogels degrade due to ester hydrolysis 17 and hydroxyl radicals 18 . The statistical results of the collagen assay showed the statistically significant difference between the 2 groups, but reepithelialization of PEG-based treatment was better than the Coloskin treatment after 14 d (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1, 15, 18] However, it is widely recognized that PEGDA hydrogels are susceptible to slow degradation in vivo and are therefore unsuitable for long-term implants. [1, 10, 19, 20]In current literature, the in vivo degradation of PEGDA hydrogels is typically attributed to hydrolysis of the endgroup acrylate esters that are introduced upon acrylation of PEG diol. However, until recently, the hydrolytic degradation profile of PEGDA hydrogels was poorly characterized, as the majority of reports on PEGDA hydrolysis referred to a study with tri(ethylene glycol) diacrylate (TEGDA).…”
Section: Introductionmentioning
confidence: 99%
“…[29] Thus, the observed degradation of PEGDA hydrogels could be a result of ester group cleavage via hydrolysis, ether cleavage via oxidation, or some combination of the two. [20, 24]…”
Section: Introductionmentioning
confidence: 99%